Perceptions of rural highlands' communitty toward agricultural mechanization : case study in Bario and Long Seridan - Jacelyn Eda Robert Bedali (2017)
The increasing world population has raised several concerns that mainly include food sustainability. The production of food if feared to decrease over due to the increase in consumers and the lack of sustainable land. Therefore, several methods have been devised and developed to help securing the global food production.
Project paper (B.S.Bi.) - Universiti Putra Malaysia, 2017
English.
Keywords: Food crops -- Malaysia -- Sarawak -- Bario; Agriculture and state -- Malaysia -- Sarawak -- Bario